Understanding Generation Z’s Shopping Interest on E-Commerce ‘T’: The Role of Usefulness, Trust, User Interface, and Ease of Use in the Bekasi Area - Adi Teguh Suprapto; Kevin Yulianto; Kendrick Kendrick (Binus Business Review, 2025)
Despite the rapid growth of Internet users in Indonesia, e-commerce has experienced a notable decline in visitor traffic, raising concerns about shifting consumer behaviors, particularly among young shoppers. The research sought to identify the key drivers and barriers influencing Generation Z’s shopping interest in e-commerce ‘T’, focusing on the Bekasi region—a rapidly urbanizing area with high digital adoption rates among youth. The research examined perceived usefulness, trust, user interface, and ease of use, applying the Technology Acceptance Model (TAM) as a theoretical foundation. Using a quantitative approach, data were collected from 150 Generation Z respondents in Bekasi through structured questionnaires. The responses were analyzed using path analysis in SPSS to determine the strength and significance of each variable’s impact on shopping interest. The results indicate that perceived usefulness (β = 0.406, p < 0.05), trust (β = 0.248, p < 0.05), and user interface (β = 0.173, p < 0.05) significantly influence shopping interest, while perceived ease of use (p > 0.05) does not have a statistically significant effect. These findings suggest that Generation Z prioritizes functional benefits (usefulness), platform reliability (trust), and an engaging digital experience (user interface design) over mere simplicity. The research contributes to existing literature by providing demographic and geographic specificity, analyzing young consumers in Bekasi, a key market often underrepresented in e-commerce research. The insights provide practical recommendations for e-commerce platforms to refine their strategy, emphasizing feature utility, trust-building mechanisms, and user interface or experience enhancements to better attract and retain young shoppers.